THE COMMUNICATIVE COMPETENCE OF UNIVERSITAS AHMAD DAHLAN PARTICIPANTS - Abas Oya (STKIP Harapan Bima, 2021)
This study aims to determine the communicative competence of UAD participants in the Joint Thesis Writing Program at USANT from March to April 2018. Specifically, it seeks answers the question “What is the communicative competence of participants along: grammatical competence, linguistic competence, sociolinguistic competence, discourse competence and strategic competence?” The study revealed the following findings: On the level of communicative competence along: grammatical competence, the level of grammatical competence of the students are “Passed” on communicative competence. Along linguistic competence, the level of this competence revealed an average weight mean 3.65 which is verbally interpreted as “Often”. Along sociolinguistic competence, the level of sociolinguistic competence revealed an average weighted 4.38 and verbal interpreted as “Always”. Along discourse competence, the level of discourse competence revealed an average weighted 3.83 and verbal interpreted as “Often”. Similarly, along strategic competence, the level of strategic competence revealed an average weighted 3.88 and verbal interpreted as “Often”. Based on the findings and conclusions of this, the recommendations are proposed, to wit: The students should establish a clear standard of basic model of communicative competence, so that to achieve the level of communicative competence easily.